Public opinion and policy on crime prevention in Europe - Klima, Noel (2012)
In this second monitor report the focus is put on people’s perceptions and attitudes on the one hand, and on priorities in crime prevention policies across Europe on the other hand. What does the general public think about the police: their relationship with the communities, their effectiveness in preventing crime, their fairness with which they wield their authoritative power, their integrity,...? What do Europeans think of the effectiveness of policies on the different levels (national vs. European)? What do they believe to be the challenges to the security in the prevention and fight against crime? These are some questions approached in this report. The information and data used to answer these questions come from the Trust in the Police & Courts Module of the European Social Survey and from the Eurobarometer surveys conducted by the European Commission. Besides these existing survey data, the EUCPN Secretariat collected some additional data from the EUCPN members on the priorities in the crime prevention policies in their countries. More specifically, questions were asked about the country’s top three priorities in crime prevention policy/strategy and compared to the country’s three most prominent crime problems based on crime statistics. Also, it was examined whether or not the top three priorities in the country’s crime prevention policy were based on statistical or recorded data, or – if not – what other basis was used to pick these priorities. And finally, some questions were added about any remarkable or new developments in the Member States over the past five years